A Qualitative Method in Identifying Academic Aspect Element of Academic Enhancement Support for Student-Athlete - Zulfadli Bin Rozali, Mohd; Bin Puteh, Saifullizam; Bin Yunus , Nur; Khan Azizuddin Khan, Thariq (International Journal of Psychosocial Rehabilitation, 2020)
Student-athletes who are enrolled at the undergraduate level in higher educational institutions in Malaysia have the challenge of raising their academic achievement. A preliminary survey shows that nearly 40 percent of student-athletes have a cumulative grade point average (CGPA) below 3.00. This study aimed to develop an academic enhancement support framework for student-athletes in Malaysian public universities. Problems, in order to improve academic achievement among student-athletes, are due to factors of academic factor that do not support the improvement of academic achievement student-athletes during their study sessions. As a result, studentathletes could not be maintained in the session of study and scholarship, and the implications from the result are they are not allowed to participate in training and also competition. Therefore, the purpose of this study was to explore elements of support that increase academic achievement for students and athletes in aspects of academics. The qualitative research approach involves 12 respondents representing academia, management institutions, and the management of student-athletes to explore elements of support that increase academic achievement in terms of academic areas for student-athletes. This data is collected through a face-to face interview, and the data analyzed based on thematic analysis by using pencil and paper to identify elements of support that increase academic achievement in aspects of academic areas. The result of the analysis found that there are 10 elements in aspects of academic areas that can help increase the academic achievement of student-athletes that enroll in undergraduate programs in Malaysian public universities. Therefore, 10 elements of support are expected to help undergraduate student-athletes at public universities improve their academic achievement.